WORLD ENGLISHES IN ENGLISH LANGUAGE TEACHING (ELT): STUDENTS’ PERCEPTIONS - Suminar, Ririn; Gunawan, Muhammad Handi (STKIP Siliwangi, 2024)
As an international language, English has various accents from various regions due to cultural and social aspects. This research aims to find out students' views on World Englishes in English Language Teaching, to investigate the benefits and difficulties in learning World Englishes in the classroom and to describe students’ suggestion for class on World Englishes. This research uses a qualitative approach. The methods used to collect data were observation, an open-ended questionnaire, and a semi-structured interview. NVivo 12 program was used to organize the data. Meanwhile, the transcribed data were analyzed using the thematic analysis method. A total of 32 second-year students majoring in English at one of the public universities in Indonesia participated in this study. The results of this study showed that most of the students had the same perceptions of World Englishes. Students stated that World Englishes is the concept of the diversity or variety of English used in each region. In addition, they said that by studying World Englishes they get some benefits. However, they also faced problems while learning the concept of World Englishes. Therefore, they gave some suggestions for learning World Englishes to help them understand World Englishes more deeply.